Analisis Perubahan Kadar Sianida dan Aktivitas Sitotoksik pada Umbi Singkong Segar yang Diolah Menjadi Tape: Analysis of Changes in Cyanide Levels and Cytotoxic Activity in Fresh Cassava Tubers Processed into Tape - Rahmat Budiman; Laode Rijai; Erwin Samsul (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Cassava in Indonesia is the third staple food after rice and corn. In addition, cassava can also be used as a process for other food products such as cassava tape, cassava crackers, opak, getuk, tapioca flour and cassava ejects. Besides containing carbohydrates, cassava also contains cyanide which is a poisonous compound. Cyanide acid is able to cause respiratory distress to death by inhibiting the performance of the respiratory enzymes, causing disturbances in the respiratory system. This study aims to determine changes in cyanide levels and cytotoxic activity in cassava tuber preparations. Qualitative analysis was performed using FeCl3 and AgNO3 reagents, quantitative tests used argentometric titration method. Meanwhile, the cytotoxic test used the Brine Shrimp Lethality Test (BSLT) method. The cyanide content test results obtained in fresh cassava were 41,56 mg, which was categorized as quite toxic, the toxicity level of fresh cassava was classified as toxic, namely 505.82 ppm. Whereas on the processed tape, the test results showed negative results containing cyanide. Cassava tuber cytotoxic test is classified as non-toxic, which is equal to 4216.96 ppm.